1984
DOI: 10.2170/jjphysiol.34.553
|View full text |Cite
|
Sign up to set email alerts
|

Peak blood lactate after 400m sprinting in sprinters and long-distance runners.

Abstract: SummaryPeak blood lactate following 400 m sprinting was determined in 8 sprinters and 8 long-distance runners.The mean velocity of 400 m run and peak blood lactate were significantly higher in the sprinters than in the long-distance runners. It was suggested that peak blood lactate may be a useful indication of anaerobic work capacity in longdistance runners, but not in sprinters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
2
3
0
1
Order By: Relevance
“…The correlations between total work done and peak blood lactate were low and nonsignificant for all laboratory tests, A similar result was obtained with the data collected in the field. These results support the findings of Ohkuwa and Miyamura (27), who examined the relationship between peak blood lactate and 400-rn sprinting times. On the other hand, Fujitsuka et al (11) demonstrated significant correlations between peak blood lactate and 100-rn (-0.65), 200-rn (-0.78), and 400-rn (-0.79) sprint running.…”
Section: Resultssupporting
confidence: 91%
“…The correlations between total work done and peak blood lactate were low and nonsignificant for all laboratory tests, A similar result was obtained with the data collected in the field. These results support the findings of Ohkuwa and Miyamura (27), who examined the relationship between peak blood lactate and 400-rn sprinting times. On the other hand, Fujitsuka et al (11) demonstrated significant correlations between peak blood lactate and 100-rn (-0.65), 200-rn (-0.78), and 400-rn (-0.79) sprint running.…”
Section: Resultssupporting
confidence: 91%
“…In the analysis, uneven weights were found in the relationships between the [La] and the distances ran with no significant correlations between the Dmax 30 and [La] max 30 (r = -0.44; p < 0.05), and significant association between the Dmax 60 at the [La] max 60 (r = -0.82; p < 0.05). This last figure can be fitted in the higher level found by other authors, with competitive performance in 400/800 s running and 30-60 s duration treadmill running (r between -0.67 and -0.89) (18)(19)(20)(21)(22) . Despite the limitations of the size of the sampling in the present study, the higher value of the association between Dmax 60 and the [La] max 60 is in accordance to the theoretical model proposed, stating that the max 60 is more dependent from the AnA than the max 30 , and it can be more adequate to deplete it.…”
Section: Discussionsupporting
confidence: 62%
“…Apesar da vasta literatura a respeito das características fisiológicas de desportistas de diferentes modalidades [6][7][8][9][10] , poucos trabalhos analisaram a influência de diferentes funções táticas sobre as características fisiológicas de futebolistas 1,2,[11][12][13][14] Assim, o presente estudo teve como objetivo comparar jogadores de futebol de diferentes posições no que diz respeito ao consumo máximo de oxigênio (VO 2 max) e limiar anaeróbio.…”
Section: Introductionunclassified